=if(d6<50,0,if(d6="غ",0,if(e6<50,0,if(e6="غ",0,if(f6<50,0,if(f6="غ",0,if(g6<50,0,if(g6="غ",0,if(h6<50,0,if(h6="غ",0,if(i6<50,0,if(i6="غ",0,if(j6<50,0,if(j6="غ",0,if(k6<50,0,if(k6="غ",0,if(l6<50,0,if(l6="غ",0,if(m6<50,0,if(m6="غ",0,if(n6<50,0,if(n6="غ",0,if(o6<50,0,if(o6="غ",0,if(p6<50,0,if(p6="غ",0,if(q6<50,0,if(q6="غ",0,if(r6<50,0,if(r6="غ",0,sum(d6*$d$4,e6*$e$4,f6*$f$4,g6*$g$4,h6*$h$4,i6*$i$4,j6*$j$4,k6*$k$4,l6*$l$4,m6*$m$4,n6*$n$4,o6*$o$4,p6*$p$4,q6*$q$4,r6*$r$4,)))))))))))))))))))))))))))))))

Cell q6 has a function that adds a product of (b6 * b4), (c4 * c6), (d6 * d4), and so on (p6 * p4)

Provided the result is zero in two cases: enter a value less than 50

Or enter a literal value

A shortcut is required for this function to function the same as the existing function

## Bookmarks